Terms of address in Hungarian How do people address strangers of the same age? - Danyi Orsolya; Fenyvesi Anna (2018)
This paper examines the correlation between the use of pronouns and address forms in modern Hungarian and the age of the interlocutors on the basis of questionnaire research. Data gathered from Hungarians born before vs. after 1985 in Hungarian are analysed and the differences in the addressing of the two age groups are discussed. The paper reports that the formality of the setting in which the addressing takes place and the gender of the interlocutors influence the addressing of strangers of the same age. The findings reveal that the older age group is more likely to use V-forms than the younger one even in less formal situations. The paper also discusses that the younger age group is more open to using T-forms with women than the older age group in every situation. The paper also reports on the use of the structure involving tetszik in modern Hungarian. In these findings, the structure was strictly used by males from the older age group when addressing women.
Keywords: Bölcsészettudományok